The Use of the Infant Breastfeeding Assessment Tool among High Risk Mothers for the Prediction of Exclusive Breastfeeding for Six Weeks Postpartum - Pawin Puapornpong; Suttha Hamontri; Siriwan Srisuwan; Sukwadee Ketsuwan; Sinutchanan Wongin (The Royal Thai College of Obstetricians and Gynaecologists, 2020)
Objectives: To find the cut-off point, sensitivity and specificity of the infant breastfeeding assessment tool to predict breastfeeding among high risk mother during six weeks postpartum. Materials and Methods: The infant breastfeeding assessment tool was translated to Thai and the validity and reliability was evaluated. Postpartum mothers who delivered at the HRH Princess Maha Chakri Sririndhorn medical center in the Nakhon Nayok province during the period of July 2014 to June 2015 and had high risk for early breastfeeding cessation were included in this study. The mothers and babies were assessed by the infant breastfeeding assessment tool at 16-24 hours postpartum. Following discharge; the exclusive breastfeeding data at the first, second and sixth weeks postpartum was collected by telephone follow-up. The cut-off point, sensitivity and specificity of the infant breastfeeding assessment tool used for exclusive breastfeeding predictions were calculated by the receiver operating characteristic curve.Results: Three hundred and sixty-one high risk mothers for early breastfeeding cessation; teenage mothers, mothers with cesarean deliveries and obese mothers were recruited in this study. The validity of the infant breastfeeding assessment tool was 93.2%. The Cronbach alpha coefficient was 82.7. The cut-off point to predict exclusive breastfeeding at the first, second and sixth weeks postpartum was determined to be 8 points. The sensitivity and specificity of tests for the first, second and sixth week exclusive breastfeeding predictions were 88.9, 88.9, 90.5% and 72.3, 72.0, 74.6%, respectively. The best prediction accuracy was 73.0 percent at the first week postpartum. The relative risk during six-week postpartum period for early breastfeeding cessation between the mothers and babies who had the infant breastfeeding assessment tool scores of less than and greater than 8 points were 1.7-2.1. Conclusion: The infant breastfeeding assessment tool can be used for the prediction of exclusive breastfeeding during the first six weeks postpartum. The accuracy of the test was best at the first week postpartum.